Moral philosophy - Maritain, Jacques (New York, Charles Scribner's Sons, 1964)
Philosophical ethics from Socrates to Sartre.
Keywords: Socrates; Aristotle; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Ethics -- History; Plato; Stoics; Christianity -- Philosophy; Kant, Immanuel; Marx, Karl; Dialectical materialism; Comte, Auguste; Positivism; Kierkegaard, Soren Aabye; Sartre, Jean Paul; Existentialism; Dewey, John; Naturalism; Bergson, Henri Louis